Implementasi Metode Alfiyah Aplikatif dalam Pembelajaran Baca Kitab Kuning di Pondok Pesantren Al-Ma’ruf Pare Kediri - Erika Mufidatul Khusna; Mulyadi (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
The Applicative Alfiyah Method is a practical method for reading and understanding the yellow book written by KH. Nurul Anwar. This Applicative Alfiyah Method The Amtsilati method summarizes the alfiyah which totals 1002 stanzas by focusing on the stanzas needed in reading writing that does not have a vowel. Applying this method can make it easier for students who have had difficulty understanding the yellow book. In this thesis there are two things discussed, namely: (1) How is the implementation of the Applicative Alfiyah method in learning to read the yellow book at Al-Ma'ruf Islamic Boarding School Pare Kediri? (2) What are the obstacles in implementing the Applicative Alfiyah method in learning to read the yellow book at the Al-Ma'ruf Pare Kediri Islamic Boarding School? The approach in this study uses a qualitative approach, while the type of research used in this study is a case study. Methods of data collection using observation, interviews, and documentation. Based on the problems described above, it can be concluded that (1) Applicative Alfiyah Method has been implemented as a method in yellow reading through several stages, namely: lesson planning, learning process, learning evaluation. (2) constraints in implementing Applicative Alfiyah method in learning read the yellow book in the Al-Ma'ruf Pare Kediri Islamic boarding school, including the ability of students who are still beginners, memorizing and students who do not obey the rules.